Acid-catalyzed esterification of Zanthoxylum bungeanum seed oil with high free fatty acids for biodiesel production - Zhang, Junhua; Jiang, Lifeng (Bioresource technology, 2008)
A technique to produce biodiesel from crude Zanthoxylum bungeanum seed oil (ZSO) with high free fatty acids (FFA) was developed. The acid value of ZSO was reduced to 1.16 mg KOH/g from 45.51 mg KOH/g by only one-step acid-catalyzed esterification with methanol-to-oil molar ratio 24:1, H 2SO 4 2%, temperature 60 °C and reaction time 80 min, which was selected as optimum for the acid-catalyzed esterification. During the acid-catalyzed esterification, FFA was converted into fatty acid methyl esters, which was confirmed by 1H NMR spectrum. Compared with the other two-step pretreatment procedure, this one-step pretreatment can reduce the production cost of ZSO biodiesel. Alkaline-catalyzed transesterification converted the pretreated ZSO into ZSO biodiesel. The yield of ZSO biodiesel was above 98% determined by 1H NMR spectrum. This study supports the use of crude ZSO as a viable and valuable raw feedstock for biodiesel production.